Impact of the Clean Air Act on Air Pollution and Infant Health: Evidence from South Korea - Soohyung Lee; Heesun Yoo; Minhyuk Nam (Institute of Labor Economics (IZA), 2018)
This paper examines the extent to which the 2005 Clean Air Act introduced in South Korea affected air pollution and infant health. To identify the causal effect, we exploit the time and geographical variations in the adoption of the Act between 2003 and 2006. During this period, the Clean Air Act indeed significantly reduced air pollutants. For example, the PM10 level was reduced by 9 percent. However, the Act's impact on infant mortality was not statistically significant.
Keywords: I18; K32; Q52; 330; air pollution; infant mortality; PM10